Enhancement of Intermediate-Temperature Strength of Corundum-Spinel Castables via Incorporation of Zn(OH)2 Powders - Dong, Yifan; He, Mantang; Sang, Mengyang; Qiu, Xin; Xu, Pengyu; Liu, Xinhong; Jia, Quanli (Materials, 2025)
Corundum-spinel based purging plugs are extensively employed in steel ladle refining processes. Traditionally, these plugs are manufactured through a high-temperature firing process that not only demanded substantial energy consumption but also resulted in a dense microstructure with higher strength; however, they often led to undesirable consequences such as fracture and thermal spalling, significantly impeding the enhancement of their service life. In recent years, the steel industry has witnessed the emergence of unfired purging plugs as an alternative solution. Unfortunately, there are some shortcomings including low strength at intermediate-temperature and poor volume stability, which easily lead to a short life and lower blowing rate of the unfired purging plug, thereby restricting their utilization. Aiming to improve the intermediate-temperature properties of the unfired purging plug, the effect of Zn(OH)2 on the properties of the castables was investigated. The results show that the cold strength of the specimens sintered at different temperatures remarkably increased with rising Zn(OH)2 content, for instance, CMOR values of the specimens sintered at 800 °C escalated from 3.19 MPa to 14.98 MPa. Furthermore, the incorporation of Zn(OH)2 led to a reduction in permanent linear change and a marked increase in hot strength. The remarkable improvement in intermediate-temperature strength can be attributed to the formation of ZnCr2O4 and ZnAl2O4 spinel phases originating from the reaction between ZnO derived from the decomposition of Zn(OH)2, and the existing Cr2O3 or Al2O3. These spinel phases create a reinforcing effect, thereby substantially enhancing the mechanical properties of the specimens after firing at intermediate temperatures.